1999
DOI: 10.1093/emboj/18.7.1905
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of transcription activation by HLF and HIF1alpha in response to hypoxia: their stabilization and redox signal-induced interaction with CBP/p300

Abstract: Hypoxia-inducible factor 1 α (HIF1α) and its related factor, HLF, activate expression of a group of genes such as erythropoietin in response to low oxygen. Transfection analysis using fusion genes of GAL4DBD with various fragments of the two factors delineated two transcription activation domains which are inducible in response to hypoxia and are localized in the C-terminal half. Their sequences are conserved between HLF and HIF1α. One is designated NAD (N-terminal activation domain), while the other is CAD (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
340
3
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 531 publications
(359 citation statements)
references
References 52 publications
14
340
3
2
Order By: Relevance
“…HIF-α subunits therefore accumulate in the cytoplasm of O 2 -starved cells, and translocate to the nucleus, where they dimerize with HIF-1β/aryl hydrocarbon receptor nuclear translocator (ARNT) through their PER-ARNT-SIM (PAS) domains (see Box 1), and bind to HIF-response elements (which contain the core recognition sequence 5'-RCGTG-3') located within the promoters, introns, and 3' enhancers of a large number of O 2 -regulated target genes. During this process the C-terminal transcriptional activation domain (TAD) also interacts with coactivators such as p300/CBP (CREB-binding protein; CREB is CRE-response element binding protein) 131 (see figure). This interaction is thought to be required for full HIF activity, but is also regulated by normoxic hydroxylation reactions; in this case at asparagine 803 (see Box 1) 132 .…”
Section: Box 2 Regulation Of Hypoxia-inducible Factor By O 2 Deprivationmentioning
confidence: 99%
“…HIF-α subunits therefore accumulate in the cytoplasm of O 2 -starved cells, and translocate to the nucleus, where they dimerize with HIF-1β/aryl hydrocarbon receptor nuclear translocator (ARNT) through their PER-ARNT-SIM (PAS) domains (see Box 1), and bind to HIF-response elements (which contain the core recognition sequence 5'-RCGTG-3') located within the promoters, introns, and 3' enhancers of a large number of O 2 -regulated target genes. During this process the C-terminal transcriptional activation domain (TAD) also interacts with coactivators such as p300/CBP (CREB-binding protein; CREB is CRE-response element binding protein) 131 (see figure). This interaction is thought to be required for full HIF activity, but is also regulated by normoxic hydroxylation reactions; in this case at asparagine 803 (see Box 1) 132 .…”
Section: Box 2 Regulation Of Hypoxia-inducible Factor By O 2 Deprivationmentioning
confidence: 99%
“…Initially, the effects of Txn1 overexpression on HIF-1α were reported to be exclusively on its transcriptional activity (Carrero et al, 2000;Ema et al, 1999;Huang et al, 1996), but, more recently, Txn1 overexpres- sion was reported to induce HIF-1α stabilization (Welsh et al, 2002;Zhou et al, 2007). In these studies, no changes in the mRNA levels of HIF-1α were reported.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide evidence that the effect of Txn1 on HIF-1α is limited to its transcriptional activity. Previously, the mutation of a cysteine in C-TAD of HIF-1α abolished its interaction with the transcriptional co-activator p300, and thus, inhibited HIF-1α transcriptional activity (Ema et al, 1999). A mechanism was proposed, wherein Txn1, through Ref-1, would reduce a cysteine in the transactivation domain of HIF-1α and allow its interaction with p300.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations